2012
DOI: 10.1194/jlr.m020883
|View full text |Cite
|
Sign up to set email alerts
|

The fibrillogenic L178H variant of apolipoprotein A-I forms helical fibrils

Abstract: A number of amyloidogenic variants of apoA-I have been discovered but most have not been analyzed. Previously, we showed that the G26R mutation of apoA-I leads to increased β-strand structure, increased N-terminal protease susceptibility, and increased fibril formation after several days of incubation. In vivo, this and other variants mutated in the N-terminal domain (residues 26 to ∼90) lead to renal and hepatic accumulation. In contrast, several mutations identified within residues 170 to 178 lead to cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 39 publications
(51 reference statements)
3
57
1
Order By: Relevance
“…We also found that the amyloid fibrils of the 1-83 fragments exhibit strong toxicity to HEK293 cells as with amyloid ␤ fibrils (40). To our knowledge, the finding that the 1-83 fragment of apoA-I forms amyloid fibrils at physiological neutral pH is quite novel because the previous observations indicated that the fibril formation of apoA-I in vitro requires the acidic condition (16,41,42), methionine oxidation (19), or amyloidogenic mutations (23,43).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We also found that the amyloid fibrils of the 1-83 fragments exhibit strong toxicity to HEK293 cells as with amyloid ␤ fibrils (40). To our knowledge, the finding that the 1-83 fragment of apoA-I forms amyloid fibrils at physiological neutral pH is quite novel because the previous observations indicated that the fibril formation of apoA-I in vitro requires the acidic condition (16,41,42), methionine oxidation (19), or amyloidogenic mutations (23,43).…”
Section: Discussionmentioning
confidence: 67%
“…In fact, our recent hydrogen-deuterium exchange and mass spectroscopy measurements of apoA-I Iowa demonstrated that the G26R mutation induces widespread structural reorganization of residues in the central region of the apoA-I molecule despite a small change in the net helical contents (47). Similarly to the G26R mutation, the fibrillogenic L178H mutation, which is also located within the N-terminal helix bundle, was shown to exhibit a decreased protein stability and an altered lipid binding profile (43). In addition, oxidation of the methionine residues of apoA-I causes the destabilization of the tertiary and quaternary structure of the protein, leading to the formation of amyloid fibrils (19).…”
Section: Discussionmentioning
confidence: 99%
“…Expression and Purification of Recombinant Human ApoA-I Human apoA-I containing a His tag at the N terminus was expressed in bacteria and purified using immobilized metal affinity chromatography followed by tobacco etch virus protease treatment to remove the His tag, as previously described (10,11). ApoA-I proteins were produced either in-house or at the Lund University Protein Production Platform (LP3).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, the apo A-I variant L178H has been shown to form fibrils with exclusively α-helical structure. 25 The L178H variant is the first report of a full-length variant of apo A-I that forms α-helical fibrils. The presence of α-helical character in physiological apo A-I fibrils indicates that this secondary structure is important in protein aggregation and disease, and suggests that our work on apo A-I mimetic peptides may inform this growing area of exploration.…”
Section: Introductionmentioning
confidence: 99%